Wildlife DNA analysis applications in forensic science - Linacre, Adrian (John Wiley & Sons Inc., 2013)
"This book is the first to approach the fast developing field of wildlife forensics with a focus on the application of DNA profiling and analysis. Case studies throughout link theory and practice and highlight the use of DNA testing in species testing. The text assumes only a basic background knowledge of DNA, so offers information boxes clarifying technical information, step-by-step guidance on sequence comparisons, and a discussion of the different markers used in species testing. This produces a highly accessible introduction for both students and forensic professionals"--